Structure Differentiation of Hydrophilic Brass Nanoparticles Using a Polyol Toolbox - Antonoglou, Orestis; Founta, Evangelia; Karagkounis, Vasilis; Pavlidou, Eleni; Litsardakis, George; Mourdikoudis, Stefanos; Thanh, Nguyen Thi Kim; Dendrinou-Samara, Catherine (Frontiers in Chemistry, 2019)
Nano-brasses are emerging as a new class of composition dependent applicable materials. It remains a challenge to synthesize hydrophilic brass nanoparticles (NPs) and further exploit them for promising bio-applications. Based on red/ox potential of polyol and nitrate salts precursors a series of hydrophilic brass formulations of different nanoarchitectures were prepared and characterized. Self assembly synthesis was performed in the presence of triethylene glycol (TrEG) and nitrate precursors Cu(NO3)2•3H2O and Zn(NO3)2•6H2O in an autoclave system, at different temperatures, conventional or microwave-assisted heating, while a range of precursor ratios was investigated. NPs were thoroughly characterized via X-ray diffraction (XRD), Thermogravimetric analysis (TGA), Scanning electron microscopy (SEM), Transition electron microscopy (TEM), Infra-red spectroscopy (FTIR), dynamic light scattering (DLS) and ζ-potential to determine the crystal structure, composition, morphology, size, state of polyol coating and aqueous colloidal stability. Distinct bimetallic α-brasses and γ-brasses, α-Cu40Zn25/γ-Cu11Zn24, α-Cu63Zn37, α-Cu47Zn10/γ-Cu19Zn24, and hierarchical core/shell structures, α-Cu59Zn30@(ZnO)11, Cu35Zn16@(ZnO)49, α-Cu37Zn18@(ZnO)45, Cu@zinc oxalate, were produced by each synthetic protocol either as stoichiometric, copper-rich and/or zinc-rich nanomaterials. TEM sizes were estimated at 20-40 nm for pure bimetallic particles and at 45-70 nm for hierarchical core/shell structures. Crystallite sizes for the bimetallic nanocrystals were found ca. 30-45 nm while in case of the core-shell structures smaller values around 15-20 nm were calculated for the ZnO shells. Oxidation and/or fragmentation of TrEG were unveiled and attributed to the different fabrication routes and formation mechanisms. All NPs were hydrophilic with 20-30% w/w of polyol coating, non-ionic colloidal stabilization (-5 mV < ζ-potential < -13 mV) and relatively small hydrodynamic sizes < 250 nm. The polyol toolbox proved effective in tailoring the structure and composition of hydrophilic brass NPs while keeping the crystallite and hydrodynamic sizes fixed.